The Arithmetic Game Application Category for Children Using General Basic Knowledge Based Methods - Hasugian, Abdul Halim; Sriani (Cattleya Darmaya Fortuna, 2023)
A computer is a series of electronic machines consisting of thousands or even millions of components that can work together and form a neat and thorough system. Technological developments in the computer sector have progressed rapidly. Many new software have been created to help make human work easier and more practical. Almost every field has been touched by computer technology, including education. The teaching system implemented by the school does not yet have complete facilities to help students learn. Students often find it difficult because they have to study certain subjects that require a lot of study and practice, such as mathematics at elementary school level. Due to the lack of complete learning facilities at school, parents can provide interesting learning facilities by using an application at home so that their children are interested in studying at home. Creating this application goes through several stages such as: problem analysis, creating a database structure, creating a menu design, creating an application and conclusions and suggestions so that you get an application that suits your wishes and is structured. The aim of creating this application is so that elementary school age children can practice answering arithmetic questions more easily and with fun.